PENGEMBANGAN MEDIA FAS LIMBAH KULIT PISANG TERINTEGRASI MATERI SIKLUS AIR UNTUK MENDUKUNG IMPLEMENTASI KURIKULUM MERDEKA SISWA KELAS V SD NEGERI 104211 MARINDAL - Emia Talenta Br Ginting; Dara Fitrah Dwi; Khairiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research focused on the development of a learning media based on FAS (Simple Water Filtration) using banana peel waste integrated with water cycle material. The term FAS stands for simple water filtration. The objectives of this research were to develop the product, assess its feasibility, and determine the students' responses to the FAS media utilizing banana peel waste integrated with water cycle material. The research adopted the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. Problems encountered in the field were identified through data collection, product development, media expert validation, material expert validation, and learning expert validation. The research subjects were 15 fifth-grade elementary school students. Data were collected through questionnaires. The development results showed the product feasibility validation scores of 78 from media experts, 80 from material experts, and 86 from learning experts, placing it in the "feasible" to "highly feasible" categories. Additionally, student response results indicated a score of 84.6, categorizing them as "highly interested" in the product. Therefore, it can be concluded that the FAS media using banana peel waste integrated with water cycle material is valid and feasible for use.